2019
DOI: 10.1029/2018jc014456
|View full text |Cite
|
Sign up to set email alerts
|

Intratidal and Fortnightly Variability of Vertical Mixing in a Macrotidal Estuary: The Gironde

Abstract: Intratidal and fortnightly variability of turbulence at the mouth of a macrotidal estuary is explored in this study. Profiles of turbulent kinetic energy dissipation were estimated from a Vertical Microstructure Profiler, and velocity shear measurements and current velocities were collected with a vessel‐mounted Acoustic Doppler Current Profiler. Gradient Richardson numbers were quantified using density measurements from a Conductivity, Temperature, Depth profiler and squared vertical shear quantified from cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…Our results also identified small-scale intermittency in near-surface turbulence driven by vertical shear that is reinforced by lateral flows associated with a channel shoal interface (Collignon and Stacey 2013) and convective instabilities from the lateral straining of density gradients (Huguenard et al 2015). Recently, Ross et al (2019) found mid-water column turbulence generated by lateral flows during slack tides, which was influenced by Coriolis acceleration in a relatively wide system. Therefore, if significant channel-shoal morphology is present or the system is dynamically wide, then the number of casts averaged in a burst should increase to reduce the effects of undersampling.…”
Section: Discussionsupporting
confidence: 71%
“…Our results also identified small-scale intermittency in near-surface turbulence driven by vertical shear that is reinforced by lateral flows associated with a channel shoal interface (Collignon and Stacey 2013) and convective instabilities from the lateral straining of density gradients (Huguenard et al 2015). Recently, Ross et al (2019) found mid-water column turbulence generated by lateral flows during slack tides, which was influenced by Coriolis acceleration in a relatively wide system. Therefore, if significant channel-shoal morphology is present or the system is dynamically wide, then the number of casts averaged in a burst should increase to reduce the effects of undersampling.…”
Section: Discussionsupporting
confidence: 71%
“…So research concerning their hydrodynamics, sediment dynamics, vegetation, fluid mud, bed evolution, and ecosystem in tidal flats is still on-going. In previous studies, much attention has been paid to the characteristics of hydro-sediment dynamics in macro-tidal turbid estuaries, such as turbulence, sediment dynamics and transport (e.g., Arndt et al, 2007;King et al, 2019;Ralston et al, 2012;Ross et al, 2019;B. Wang et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Tidal pumping dominates suspended particle matter transport in well-mixed estuarine systems (Becherer et al, 2016). However, much attention has been paid on hydro-sediment dynamics in the macro-tidal estuaries (e.g., Jalón-Rojas et al, 2021;Ross et al, 2019;Tu et al, 2019), as well as the effects of tidal flat on hydro-sediment dynamics (e.g., Gao et al, 2018;Nidzieko & Ralston, 2012;Schaefer et al, 2022b). Large-scale morphodynamic behavior, such as that found in HZB, has been insufficiently examined.…”
mentioning
confidence: 99%
“…In estuaries, near-surface mixing can arise from lateral processes that is decoupled from bottom stress. The lateral straining of velocity shears, lateral density gradients and Coriolis acceleration have all promoted vertical mixing to form near the surface or subsurface during mid to late ebb [17][18][19]. These previous studies have highlighted the importance of channel-shoal morphology in the development of mixing driven by lateral processes.…”
Section: Introductionmentioning
confidence: 92%